2020
DOI: 10.1158/1078-0432.ccr-19-1247
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Prognosis of Patients with Pancreatic Cancer by Machine Learning

Abstract: Purpose: Pancreatic cancer remains a disease of high mortality despite advanced diagnostic techniques. Mucins (MUC) play crucial roles in carcinogenesis and tumor invasion in pancreatic cancers. MUC1 and MUC4 expression are related to the aggressive behavior of human neoplasms and a poor patient outcome. In contrast, MUC2 is a tumor suppressor, and we have previously reported that MUC2 is a favorable prognostic factor in pancreatic neoplasia. This study investigates whether the methylation status of three muci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…In pancreatic cancer, the transcription factor hif- 2α can speed up metabolism and promote tumor proliferation and high level of hif- 2α correlates with worse OS [ 61 , 62 ]. The methylation status of GRAP2 , ICAM3 , A2ML1 , MUC1, and MUC4 can influence the expression of these genes, which is associated with survival of pancreatic cancer [ 63 , 64 ]. Phosphatidylserine is related to apoptosis of pancreatic cancer cells with the involvement of microparticles [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, the transcription factor hif- 2α can speed up metabolism and promote tumor proliferation and high level of hif- 2α correlates with worse OS [ 61 , 62 ]. The methylation status of GRAP2 , ICAM3 , A2ML1 , MUC1, and MUC4 can influence the expression of these genes, which is associated with survival of pancreatic cancer [ 63 , 64 ]. Phosphatidylserine is related to apoptosis of pancreatic cancer cells with the involvement of microparticles [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed that the expression of several DNA methylation/demethylation factors have a signi cant correlation with MUC1 methylation status. Subsequent studies also concluded that aberrant methylation of MUC1 promoters are potential prognostic biomarkers for pancreatic ductal adenocarcinomas [49]. DNA methylation refers to the chemical modi cation that transfers methyl to speci c bases in the DNA chain under the action of DNA methylase.…”
Section: Discussionmentioning
confidence: 99%
“…For pancreatic cancer, the transcription factor, hif-2α, can speed up metabolism and promote tumor proliferation and high level of hif-2α correlates with worse patients OS (61,62). Methylation status of GRAP2, ICAM3, A2ML1, MUC1 and MUC4 can in uence expression of these genes, which is associated with survival of pancreatic cancer (63,64). Phosphatidylserine is related to the apoptosis of pancreatic cancer cells with the intervention of microparticles (65).…”
Section: Discussionmentioning
confidence: 99%